Side-Channel Attack on ARADI in Non-Profiling Scenarios - Donggeun Kwon; Seokhie Hong (IEEE Access)
ARADI is a low-latency block cipher introduced by the NSA (National Security Agency), designed with consideration for applications in memory encryption. In this study, we present the first results of side-channel attacks on ARADI, exposing its vulnerabilities to physical attacks in a non-profiling scenario. We propose a novel bitwise divide-and-conquer methodology tailored for ARADI, and extend the approach to recover the full 256-bit master key. Using power consumption traces from an ARM processor, our experimental results demonstrate the effectiveness of our attack method, achieving key recovery with only 2,000 traces. These findings highlight critical weaknesses in the physical security of ARADI and emphasize the need for robust countermeasures to address side-channel vulnerabilities without compromising performance. This research provides new insights into the practical security of ARADI, underscoring the importance of integrating physical attack resilience in cryptographic designs.